Kombinasi Terapi Guided Imagery dan Slow Deep Breathing dengan Perubahan Tekanan Darah Pada Lansia Hipertensi Grade II - Wahyu cahyono; Sukardin; Hildayanti; Ageng Abdi Putra; Sri hardiani; Nurul Ilmi (LPPM STIKES Mataram, 2024)
Introduction: Hypertension in the elderly is a condition where a person experiences an increase in blood pressure above normal, either systolic or diastolic pressure. A higher systolic pressure above 140 mmHg or a higher diastolic pressure above 90 mmHg is considered hypertension. Guided imagery or guided imagination is a mind-body technique that is guided through concentration and imagination of the mind. Meanwhile, slow deep breathing is conscious relaxation to regulate breathing deeply and slowly. Purpose: The aim of this study was to determine the combination of guided imagery and slow deep breathing therapy on changes in blood pressure in elderly with grade II hypertension. Method: This type of research is pre-experimental research with the design used in this research, namely a one group pretest-posttest design. The population of this study were all elderly people who had grade II hypertension with a total of 60 elderly people. The research sample of 26 elderly people was obtained using purposive sampling techniques and inclusion and exclusion criteria. The research instruments used SOP and a mercury tensimeter and a statescope. Therapy was carried out for 3 weeks. 1 week of the BHSP process, then therapy is given twice a day for 2 weeks. Data analysis used the Wilcoxon Signed Ranks Test. Result: the research results showed that the average difference in systolic blood pressure before and after treatment was 13.50 mmHg. The average difference in diastolic blood pressure before and after treatment was 13.76 mmHg. The statistical test results are significant value (p) = 0.000.